Analysis of stress-causing factors in the final undergraduate year of the nursing course - doi 10.4025/actascihealthsci.v34i2.9209 - Barboza, Marcela Corrêa; Soares, Marcos Hirata (Acta Scientiarum. Health Sciences, 2012)
An exploratory and descriptive study that analyzed the intensity of stress caused by different situations is provided. The sample consisted of 47 final-year nursing students at the State University of Londrina and was carried out between July and September 2009. Data, obtained by a seven-item visual analogue scale and by a single open question on the perception of other stress sources, were analyzed through rating scores and resulted in a data table. Most students were rated at intensity 3 (38.3%) and 4 (36.2%), or rather, maximum overload stress for academic studies. Lack of leisure time and fear of unemployment after graduation were regarded as stress-causing situations, coupled to a feeling of being unprepared to exercise one’s profession. Financial difficulties led to lower intensity but medium-significance factors for stress development. Interpersonal relationships received the lowest intensity scores. Results indicated future changes in the curriculum of the nursing course to minimize the suffering and harm to the students’ mental health and to provide the full development of their emotional maturity.